2002
DOI: 10.3354/meps226301
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of bacterial strains isolated from marine biofilms in Hong Kong waters for the induction of larval settlement in the marine polychaete Hydroides elegans

Abstract: In the present study, 38 bacterial isolates were obtained from a marine biofilm, identified by the comparison of 16S rRNA gene sequences, and investigated by laboratory bioassays for their effects on larval settlement of the marine polychaete Hydroides elegans (Haswell). The bacterial isolates belonged to 3 phylogenetic branches: γ-Proteobacteria (26 isolates), Gram-positive (8 isolates) and Cytophaga-Flexibacter-Bacteroides (4 isolates). Most of the isolates were affiliated to the genera Vibrio (7 isolates), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
96
1
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 39 publications
5
96
1
2
Order By: Relevance
“…It has long been known that biofilms are one of the major sources of settlement cues for the larvae of Hydroides elegans. Although natural multispecies biofilms induce the settlement of this species (Lau et al 2005), monospecies biofilms can have an inductive, neutral or inhibitive effect on settlement (Unabia & Hadfield 1999, Lau & Qian 2001, Lau et al 2002, 2003a, Huang & Hadfield 2003, Lee & Qian 2003. All these results were obtained from laboratory experiments.…”
Section: Discussionmentioning
confidence: 75%
“…It has long been known that biofilms are one of the major sources of settlement cues for the larvae of Hydroides elegans. Although natural multispecies biofilms induce the settlement of this species (Lau et al 2005), monospecies biofilms can have an inductive, neutral or inhibitive effect on settlement (Unabia & Hadfield 1999, Lau & Qian 2001, Lau et al 2002, 2003a, Huang & Hadfield 2003, Lee & Qian 2003. All these results were obtained from laboratory experiments.…”
Section: Discussionmentioning
confidence: 75%
“…However, in the presence of antibiotics, these amino acids showed the same inductive effects as when without antibotics, suggesting that larval metamorphosis was directly triggered by amino acids. Although the bacterial density was relatively high in the treatments without antibiotics, the bacteria did not show inductive Since previous studies demonstrated that many bacterial strains had no inductive effects on the larval metamorphosis of Hydroides elegans (Lau et al 2002), one may speculate that these amino acids may selectively promote the growth of bacteria that have no direct effects on larval settlement and metamorphosis of H. elegans. Further work on the community structure analysis of bacterial biofilms, developed under different treatments of amino acids, will provide insight into the composition of inductive, non-inductive and even inhibitive bacterial strains.…”
Section: Discussionmentioning
confidence: 94%
“…On smaller spatial scales, active larval behavior such as substrate rejection or substratum exploration determines the success of larval settlement, particularly when larvae descend to the sea floor. Larvae of many marine invertebrates require specific cues to settle and metamorphose and cues can originate from conspecific or congeneric individuals (Crisp 1984, Pawlik 1992, Rodriguez et al 1993, Qian 1999, microbial films (Kirchman et al 1982a, Maki et al 1989, Lau et al 2002, sympatric species, food items, habitat (Bryan et al 1998), and other environmental sources (Pechenik et al 1995). A variety of chemicals have been suggested to be cues that include juvenile hormones (Biggers & Laufer 1992, 1996, free fatty acids (Pawlik 1986, Pawlik & Faulkner 1986, 1988), polysaccharides (Kirchman et al 1982b), protein and small peptides , amino acids , inorganic ions (Yool et al 1986, Bryan et al 1997b, and neurotransmitters other than amino acids (Pawlik 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies (Unabia and Hadfield, 1999;Lau et al, 2002) have isolated bacterial strains that induce H. elegans larval settlement. However, the presence of inductive bacterial strains in a natural biofilm does not necessarily explain this biofilm's inductiveness.…”
Section: Discussionmentioning
confidence: 99%